An In Silico Target Fishing Approach to Identify Novel Ochratoxin A Hydrolyzing Enzyme - Luca Dellafiora; Christoph Gonaus; Barbara Streit; Gianni Galaverna; Wulf-Dieter Moll; Gudrun Vogtentanz; Gerd Schatzmayr; Chiara Dall’Asta; Shreenath Prasad (Toxins, 2020)
Ochratoxin A (OTA), a mycotoxin that is of utmost concern in food and feed safety, is produced by fungal species that mainly belong to the Aspergillus and Penicillium genera. The development of mitigation strategies to reduce OTA content along the supply chains is key to ensuring safer production of food and feed. Enzyme-based strategies are among the most promising methods due to their specificity, efficacy, and multi-situ applicability. In particular, some enzymes are already known for hydrolyzing OTA into ochratoxin alpha (OTα) and phenylalanine (Phe), eventually resulting in detoxification action. Therefore, the discovery of novel OTA hydrolyzing enzymes, along with the advancement of an innovative approach for their identification, could provide a broader basis to develop more effective mitigating strategies in the future. In the present study, a hybrid in silico/in vitro workflow coupling virtual screening with enzymatic assays was applied in order to identify novel OTA hydrolyzing enzymes. Among the various hits, porcine carboxypeptidase B was identified for the first time as an effective OTA hydrolyzing enzyme. The successful experimental endorsement of findings of the workflow confirms that the presented strategy is suitable for identifying novel OTA hydrolyzing enzymes, and it might be relevant for the discovery of other mycotoxin- mitigating enzymes.